Real-time PCR detection of Coxiella burnetii in dairy products in Kwara State, Nigeria: a public health concern - Nusirat Elelu; Nwachukwu Raymond Chinedu; Balkees A. Yakub-Obalowu; Ismail A. Odetokun; Ahmad I. Al-Mustapha (BMC Veterinary Research)
Abstract Background Coxiella burnetii is the etiological agent of Q fever in humans, a zoonosis of increasingly important public health concern. The disease results in significant economic losses to livestock farmers and its presence in ready-to-eat dairy products poses a public health threat to consumers. Aim This study aimed to detect Coxiella burnetii in dairy products in Kwara State, Nigeria. Methods A cross-sectional study was performed to estimate the apparent and true prevalence of C. burnetii in dairy cattle in selected local government areas (LGAs) of Kwara State, Nigeria. A total of 51 traditional Fulani transhumance farms were sampled across three regions: 27 farms in Ifelodun LGA, 9 in Ilorin East LGA, and 15 in Moro LGA. Four pooled milk samples were collected aseptically from lactating cows on each farm, totaling 204 milk samples. We screened the pathogen using real-time PCR that targeted the IS1111 element in the 51 pooled raw milk samples from selected farms and 18 cheese samples from rural markets within the study area. Results The overall apparent prevalence of C. burnetii in milk and cheese was 18.8%. Both dairy products showed similar prevalence with a relatively higher positivity rate in cheese (22.2%, n = 4/18) than in raw milk samples (17.6%, n = 9/51). There were significant differences in the burden of C. burnetii in milk between the three LGAs with higher prevalence in Moro LGA (p < 0.05). Conclusions The presence of C. burnetii in dairy products poses a direct risk of milk-borne zoonotic disease transmission to humans. Public education for the stakeholders in the dairy value chain should be intensified and the public should desist from consumption of unpasteurized milk. More molecular studies are needed to further study and characterize the C. burnetii genotypes in Nigeria.